Ардчилсан нийгэм дэх бие хүний сэтгэл зүй, төлөвшил - Д.Отгонхишиг (Politology, 2023)
Товч хураангуй: Ардчилсан чөлөөт нийгэмд хүмүүс амьдрахдаа хүн болж төлөвших явцад, хэрхэн авъяасаа хөгжүүлж нийгэмтэйгээ хөл зэрэгцэн алхах, нийгмийн хөгжлийг дагаад өөрийгөө хэрхэн хөгжүүлсэн санааг дэвшүүлсэн болно. ABSTRAST Every citizen’s an active activity and their knowlesage, talent and also now their personality is formed which is influenced to ensure democratic social criteria. It’s very important to live in conformity with the requirement being political politeness. As well as social range and social organization play main role to involve citizen in politic especially personal psychology, her and his talent ability, education or progress of personal psyche and physique and to form educational positive nowadays it satisfied thal learning to express oneself truly to others as result of personal talent and education, physique is perfected.